Differences in The Effectiveness of Electroacupuncture and Fire Cupping on Knee Pain Among of The Seliwerun Running Club, Bandung City - Abdurrachman Taufiq; Ros Endah Happy Patriyani; Jatmiko Rinto Wahyudi (HAKTI : Indonesian Acupuncture Therapists Association, 2026)
Knee pain was frequently experienced by runners due to repetitive activities. Electroacupuncture (EA) and fire cupping (FC) were non-pharmacological methods commonly used for knee pain management; however, comparative evidence regarding their effectiveness remained limited. This study aimed to analyze the differences in effectiveness between EA and FC in reducing knee pain among runners of the Seliwerun Running Club, Bandung City. A quasi-experimental study with a pretest–posttest design was conducted. A total of 30 runners were divided into EA and FC groups (n = 15 each). The interventions were administered six times over three weeks. Knee pain was measured using the WOMAC questionnaire. Data were analyzed using the Paired Sample t-test and Independent Sample t-test. The Paired Sample t-test showed that both groups experienced a significant reduction in WOMAC scores (p < 0.001) (EA: mean 34.33 ± 2.55, t = 52.061; FC: mean 29.40 ± 2.23, t = 51.068). The mean reduction in WOMAC score in the EA group (34.33) was greater than that in the FC group (29.40). The Independent Sample t-test indicated a significant difference between the two groups (p < 0.001, t = –9.185, mean difference = –4.600), with a reduction difference of 4.93. Electroacupuncture was more effective than fire cupping in reducing knee pain among runners.